2014
DOI: 10.1208/s12249-014-0077-z
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy, Pharmacokinetics, and Biodistribution of Thermosensitive Chitosan/β-Glycerophosphate Hydrogel Loaded with Docetaxel

Abstract: Abstract. Docetaxel (DTX) is a widely used anticancer drug for various solid tumors. However, its poor solubility in water and lack of specification are two limitations for clinical use. The aim of the study was to develop a thermosensitive chitosan/β-glycerophosphate (C/GP) hydrogel loaded with DTX for intratumoral delivery. The in vitro release profiles, in vivo antitumor efficacy, pharmacokinetics, and biodistribution of DTX-loaded C/GP hydrogel (DTX-C/GP) were evaluated. The results of in vitro release stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Modifications of chitosan chemistry or solutions can improve the interaction with bioactive elements and improve cell attachment . The addition of β‐glycerolphosphate (β‐GP) increased the pH of chitosan solutions to a neutral value without phase separation . The formation of 3D structures plays an important role in the utility of chitosan‐based systems.…”
Section: Introductionmentioning
confidence: 99%
“…Modifications of chitosan chemistry or solutions can improve the interaction with bioactive elements and improve cell attachment . The addition of β‐glycerolphosphate (β‐GP) increased the pH of chitosan solutions to a neutral value without phase separation . The formation of 3D structures plays an important role in the utility of chitosan‐based systems.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al developed a thermosensitive chitosan/β-glycerophosphate (C/GP) hydrogel loaded with docetaxel DTX for intratumoral delivery [108]. In vivo study of DTX-loaded C/GP hydrogel (DTX-C/GP) at 20 mg/kg in H22 tumorbearing mice demonstrated significant reduction in tumor volume.…”
Section: Hydrogelsmentioning
confidence: 99%
“…Thermosensitive hydrogels made of various polymers and biopolymers have been widely investigated as a system of local drug delivery. Among them, chitosan/glycerophosphate (Ch/Gp) hydrogel has emerged as a unique kind of injectable thermosensitive hydrogel owing to its excellent properties, including ready availability, biocompatibility, biodegradability, as well as non-toxicity (Ghasemi-Tahrir et al 2015 ; Li et al 2014 ). Therefore, thermosensitive Ch/Gp hydrogel is a good candidate for implantation of antibiotic loaded polymeric systems directly to the site of infection.…”
Section: Introductionmentioning
confidence: 99%